Patients’ thoughts on effective psychotherapy - Lindgren, Ola; Almqvist, Kjerstin; Folkesson, Per (European Journal for Qualitative Research in Psychotherapy, 2014)
Earlier studies of patients’ experiences in psychotherapy identify relationship factors as being significant for patients. Our aim in this study conducted in accord with grounded theory, was to explore in some depth patients’ thoughts about what is effective in psychotherapy and thereby increase our knowledge about the process of psychotherapy from a patient perspective. Data were collected in open interviews that provided rich and varied information. Several informants had been in more than one therapy and thus, eight interviews provided data about sixteen psychotherapies. The core concept that emerged from the data was that of the therapist’s responsive acceptance. This concept provides an answer to the question “What do patients think is effective in psychotherapy?” If the therapist is responsive and accepting, the mutual interplay between the patient and the therapist becomes productive and collaborative. On the other hand, if responsive acceptance falters, the whole therapy process is at risk.